Clostridioides difficile infection epidemiology and clinical characteristics in COVID-19 pandemic - Vázquez-Cuesta, Silvia; Olmedo, María; Reigadas, Elena; Alcalá, Luis; Marín, Mercedes; Muñoz, Patricia; Bouza, Emilio (Frontiers in Medicine, 2022)
Information on Clostridioides difficile infection (CDI) in patients with COVID-19 is scarce and points to an overall decrease of episodes during the pandemic. This situation results paradoxical, as COVID-19 patients had long periods of hospital stay and high use of antibiotics. We conducted a retrospective study from January 1st 2019 to December 31st 2020 comparing the incidence of hospital-acquired episodes of CDI (HA-CDI) among patients with and without COVID-19 admitted to our institution. During the study period, we had 82,710 admissions of non-COVID-19 cases and 6,763 of COVID-19 patients. We had 68 episodes of HA-CDI in COVID-19 patients (14.75/10,000 days) and 397 among patients with conditions other than COVID-19 (7.79/10,000 days). Comparison of HA-CDI in COVID-19 and non-COVID-19 patients indicate it occurs more frequently, more severely, and with higher recurrence among patients with COVID-19.